Secrets of confident communicators : techniques to be heard 50 - Mather, Diana (London : Teach Yourself, 2014)
What do highly successful communicators know that the rest of us don'te Do they have a secret recipe for success? Is there a special alchemy at work? Whatever your situation or motivation, 'Secrets of Confident Communicators' reveals the 50 things you need to know to express yourself with assurance and get your message across effectively. Some will surprise you, and all will inspire you. Put these 50 simple strategies together and you have a recipe for brilliant communication skills, a proven formula that will unlock the secrets and uncover your potential.
Keywords: Communication; Self-confidence.